Adults With Complex Congenital Heart Disease: Cerebrovascular Considerations for the Neurologist - Smith, Jonathan M. C.; Andrade, Jason G.; Human, Derek; Field, Thalia S. (Frontiers in Neurology, 2019)
As infant and childhood mortality has decreased in congenital heart disease, this population is increasingly reaching adulthood. Adults with congenital heart disease (ACHD) represent a group with increased risk of stroke, silent brain infarcts, and vascular cognitive impairment. Cyanotic and other complex cardiac lesions confer the greatest risk of these cerebrovascular insults. ACHD patients, in addition to having an increased risk of stroke from structural cardiac issues and associated physiological changes, may have an accelerated burden of conventional vascular risk factors, including hypertension and impaired glucose metabolism. Adult neurologists should be aware of the risks of clinically evident and subclinical cerebrovascular disease in this population. We review the existing evidence of primary and secondary stroke prevention and acute stroke treatment in these individuals, and identify knowledge gaps in need of further research.